Transdiagnostic Assessment of Temporal Experience (TATE) in mental disorders - empirical validation and adaptation of a structured phenomenological interview - Szuła, Anastazja; Moskalewicz, Marcin; Stanghellini, Giovanni (Journal of Clinical Medicine, 2024)
Abnormal experiences of time (ATEs) are an established object of research in phenomenological psychopathology. Objective: The purpose of this study was the first validation of the Transdiagnostic Assessment of Temporal Experience (TATE), a structured phenomenological interview concerning ATEs in individuals with diverse mental health conditions, and its adaptation for the Polish language. Methods: The research employed a mixed-method approach and consisted of several phases including (1) consensual translation; (2) construct and content validation by an expert panel; (3) direct feedback from patients with lived experiences of alcohol addiction, borderline personality, autism, and clinical depression; (4) an auditorium questionnaire with 98 respondents without mental health issues, who were both interviewed and gave qualitative feedback; and (5) a final expert panel and approval. Results: Following multiple stages of modification, the final TATE demonstrates strong internal consistency and validity (Cronbach’s α = 0.9), with strong correlations between the frequency, intensity, and impairment of various forms of ATEs as well as their rare occurrence among healthy participants. Conclusions: TATE represents a multidimensional and structured quantitative phenomenological approach to temporal experience for psychiatry and clinical psychology. This article presents the validated version of TATE for Polish alongside updated administration guidelines. It is now the state-of-the-art TATE that may be further adapted to other languages, including English.
Gesehen am 30.06.2025